Emotional Quotient vs Lingkungan Sekolah: Manakah yang Lebih Dominan dalam Meningkatkan Kinerja Guru? - Novita Irawati; Bambang Budi Wiyono; Siti Romlah (Universitas Kristen Satya Wacana, 2025)
Education is a conscious and planned effort to develop students’ potential through effective learning. In this process, teachers play a crucial role, as the success of education largely depends on their competence. However, despite many teachers having good emotional intelligence, their performance may still fall short without support from a conducive school environment. This study examines the influence of emotional intelligence and school environment on the performance of public junior high school teachers in Probolinggo City. The research method used was quantitative. A total of 96 junior high school teachers in Probolinggo City were the subjects of this study. The data analysis technique was carried out in several stages of testing, namely the validity test to measure the validity of the instrument using product moment correlation, and the reliability test using the Cronbach's Alpha method. The data were then analyzed using the classical assumption test which includes normality, multicollinearity, and heteroscedasticity tests. Further analysis was conducted using multiple linear regression (regression test, f test, and t test). The results revealed that emotional intelligence alone did not significantly affect teacher performance (p = 0.269 > 0.05), while the school environment did (p = 0.000 < 0.05). Simultaneously, both variables significantly influenced performance, indicated by an F value of 24.422 > F table 3.18. These findings highlight the dominant role of the school environment in enhancing teacher performance. Moreover, the interaction between emotional intelligence and a supportive environment can collectively improve the quality of teaching.